European penology or European penologies? - Hacin, Rok (European journal of criminology, 2025)
This article explores the penological map of Europe to frame European penology, based on cultural particularities that define the penal practice. One of the main characteristics of the European continent is its diversity, which is not solely reflected in the cultural particularities of nation-states, but also in the specificity of the criminal justice systems and especially the implementation of penal sanctions. Deriving from a theoretical viewpoint, penology as an academic discipline has several definitions, but in a broader sense, it can be defined as the science of penalties and sanctioning. European countries are unique in their abolitionist stance towards the death penalty, and adherence to the international regulations regarding detention and protection of detained persons? rights imposed by the Council of Europe and monitored by the European Committee for the Prevention of Torture and Inhuman or Degrading Treatment or Punishment. However, European countries are also distinct in the ways of punishing delinquents and especially implementing sanctions. Analysis of penal statistics (SPACE I and SPACE II) shows that European countries are as diverse as they can be, ranging from punitive to mild/progressive. The organisation of prison services, level of professionalism, treatment of prisoners, and the size and characteristics of prison and probation populations support the claim of multiple European penologies.